2019
DOI: 10.1213/ane.0000000000003648
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hydroxocobalamin (Vitamin B12a) in Patients With Vasopressor Refractory Hypotension After Cardiopulmonary Bypass: A Case Series

Abstract: Hydroxocobalamin (vitamin B12a) is an emerging treatment for vasoplegic syndrome (VS) associated with cardiopulmonary bypass (CPB). Given its cost and scarcity, an institutional guideline for its use as a rescue treatment in cases of suspected VS was developed. Hemodynamic variables and vasopressor requirements were reviewed for a series of 24 post-CPB patients who received B12a. Favorable changes in hemodynamic parameters and vasopressor requirements were seen after B12a administration although guideline crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 11 publications
3
45
0
1
Order By: Relevance
“…Recently, hydroxocobalamin (vitamin B12a) has been studied in patients with refractory hypotension after CPB . Cobalamins are direct inhibitors and binders of NO and likely functioning as direct inhibitors of NO synthase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, hydroxocobalamin (vitamin B12a) has been studied in patients with refractory hypotension after CPB . Cobalamins are direct inhibitors and binders of NO and likely functioning as direct inhibitors of NO synthase.…”
Section: Discussionmentioning
confidence: 99%
“…47 Recently, hydroxocobalamin (vitamin B12a) has been studied in patients with refractory hypotension after CPB. 49,50 Cobalamins are direct inhibitors and binders of NO and likely functioning as direct inhibitors of NO synthase. It is unclear if hydroxocobalamin has any direct effect on atrial natriuretic peptide or adenosine triphosphate sensitive potassium channel activity beyond the NO-mediated portions of their mechanisms.…”
Section: Prescription Of Rasi (Aras and Ace Inhibitors) Is Common Andmentioning
confidence: 99%
“…Even though H 2 S levels have been shown to be elevated in observational human septic shock studies, there are no reports of using IV hydroxocobalamin in human septic shock. Human data for IV hydroxocobalamin are limited to single case reports and case series in patients with post‐CPB vasodilatory shock (Table ) …”
Section: The Interaction Between Vitamin B12 and Circulating Gasotranmentioning
confidence: 99%
“…In the first (and largest) case series, Shah et al reported 24 of 33 cardiac surgery patients with a median CPB time of 202 minutes (interquartile range 143–237 minutes) had at least a 33% reduction in vasopressor dose at 30 minutes . In the second case series, Armour et al reported a 14 mmHg mean difference in systolic blood pressure between 30 minutes before and 30 minutes after hydroxocobalamin administration in 24 cardiac surgery patients (95% confidence interval 6‐23 mmHg, P ‐value = 0.003) …”
Section: The Interaction Between Vitamin B12 and Circulating Gasotranmentioning
confidence: 99%
See 1 more Smart Citation